Direito internacional do mar, medidas conservatórias e preservação do meio ambiente marinho - Souza, Haiany Serraggio de (My University, 2023)
The gradual incorporation of international community's environmental perspective resulted in the creation of some soft and hard law instruments, including the United Nations Convention on the Law of the Sea (UNCLOS). Faced with a scenario of repeated State practices that reflect on environmental degradation, this study aims to discuss article 290 of the UNCLOS as a way of curbing environmental threats, having established the following research problem: How is the institute of Provisional Measures provided in Article 290 of the UNCLOS capable of preventing or impeding the continuation of serious damage to the marine environment? The general objective is to investigate the relationship between the International Law of the Sea and Provisional Measures in the preservation of the marine environment. The specific objectives were delimited as: 1) To analyze the preservation of the marine environment in the International Law of the Sea; 2) Investigate Provisional Measures as an instrument for preserving the marine environment in the International Law of the Sea. As a methodology for this research, the deductive research method was employed, along with exploratory, bibliographical and documental research technique, using the judgments of the International Tribunal for the Law of the Sea, the international doctrine and the Virginia Commentaries. It was concluded that, despite the nomenclature "provisional measures" having been used to translate the aforementioned institute into Brazilian legislation, it is not sufficient to cover the environmental dimension of the institute, thus opting to refer to it as "conservative measures", since they act in favor of the conservation of both rights and the marine environment. Still, it was understood that these measures interfere on two levels, both in the conservation of the marine environment and on the preservation of the rights of the parties, which results in a cautious approach of the International Tribunal for the Law of the Sea in its decisions, valuing, in the expressive majority of the cases in which the measures were granted, in maintaining the status quo of the controversy and reinforcing, only in a procedural way, the duty of cooperation between the States. [resumo fornecido pelo autor]
A incorporação paulatina e gradual da perspectiva ambiental da comunidade internacional resultou na criação de diversos instrumentos de soft e hard law, dentre os quais a Convenção das Nações Unidas sobre o Direito do Mar (CNUDM). Diante de um cenário de reiteradas práticas Estatais cujo reflexo é a degradação ambiental, a presente dissertação volta-se ao estudo do artigo 290 da CNUDM como forma de frear ameaças ambientais, tendo sido estabelecido o seguinte problema de pesquisa: De que forma o instituto de medidas conservatórias previsto no artigo 290 da Convenção das Nações Unidas sobre o Direito do Mar revela-se apto a prevenir ou a impedir a continuidade de graves danos ao meio ambiente marinho? O objetivo geral consiste em investigar a relação entre o Direito Internacional do Mar e as Medidas Conservatórias na preservação do meio ambiente marinho. Os objetivos específicos foram delimitados em: 1) Analisar a preservação do meio ambiente marinho no Direito Internacional do Mar; 2) Investigar as Medidas Conservatórias como instrumento de preservação do meio ambiente marinho no Direito Internacional do Mar. Como metodologia da presente pesquisa, empregou-se o método de pesquisa dedutivo, com técnica de pesquisa exploratória, bibliográfica e documental, utilizando-se os julgados do Tribunal Internacional do Direito do Mar, a doutrina internacional e os Comentários de Virgínia. Concluiu-se que, em que pese a nomenclatura "medidas provisórias" tenha sido utilizada para traduzir o referido instituto na legislação brasileira, não se revela suficiente para abranger a dimensão ambiental do instituto, optando-se, assim, por referir-se a ele como "medidas conservatórias", uma vez que atuam em prol da conservação tanto de direitos, como do meio ambiente marinho. Ainda, entendeu-se que as medidas conservatórias interferem em dois níveis, tanto na conservação do meio ambiente marinho, como na preservação de direitos das partes, o que resulta em uma abordagem cautelosa do Tribunal Internacional do Direito do Mar nas suas decisões, prezando, na maioria expressiva dos casos em que as medidas foram concedidas, na manutenção do status quo da controvérsia e reforçando, apenas de forma procedimental, o dever de cooperação entre os Estados. [resumo fornecido pelo autor]
Keywords: Direito do mar; Recursos marinhos - Conservação - Legislação; Direito internacional público; Meio ambiente - Preservação; Tribunais internacionais; Law of the sea; Marine resources conservation - Law and legislation; International law; Environment - Preservation; International courts